Business gamification for dummies - Duggan, Kris (John Wiley & Sons, Inc., 2013)
The easy way to grasp and use gamification concepts in business Gamification is a modern business strategy that leverages principles from games to influence favorable customer behavior on the web in order to improve customer loyalty, engagement, and retention. Gamification can be used by any department in a company (HR, Sales, Marketing, Engineering, Support, etc.), for any web-based experience (mobile, website, retail, community, etc.). Business Gamification For Dummies explains how you can apply the principles of this strategic concept to your own business model. How gamification evolved from Farmville/Zynga and Facebook and is now something that can be applied to the work environment How to build a successful gamification program How to entice and retain customers using gamification How to drive employee behavior inside your organization Real-world illustrations of gamification at work If you're interested in learning more about this exciting and innovative business strategy, this friendly, down-to-earth guide has you covered.
Includes index. - Print version record
Keywords: Internet marketing -- Social aspects; Consumer behavior -- Social aspects; Computer games -- Social aspects; Atarazanas; Valencia; Marketing sur Internet; Aspect social; Consommateurs; Comportement; Aspect social; BUSINESS & ECONOMICS; E-Commerce; Internet Marketing; BUSINESS & ECONOMICS; Mail Order; BUSINESS & ECONOMICS; Marketing; Direct; BUSINESS & ECONOMICS; Marketing; Multilevel; BUSINESS & ECONOMICS; Marketing; Telemarketing; Computer games; Social aspects; Consumer behavior; Social aspects; Verbraucherverhalten; Spiel; Motivation; Online-Marketing; Computerspiel